2021
DOI: 10.1002/sd.2185
|View full text |Cite
|
Sign up to set email alerts
|

Gift economy and well‐being: A mode of economy playing out in recovery from Rwandan tragedies

Abstract: Previous studies challenge the assumption that economic growth improves subjective well-being, and argue that economic growth is incompatible with not only nature conservation but also subjective well-being. To achieve SDGs, a mode of economy that sustains both subjective well-being and the natural environment needs to be investigated. This ethnographic study explored community-based economy systems in post-genocide Rwanda, and elaborated the process and mechanisms by which the contemporary gift economy facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In Japanese culture, buying food from seven neighbours for a 7-year-old child is interpreted as sacrificing power from others (Befu, 1968). A tribe in Rwanda sees the gift given to them as a gift from god because of the well-being of gift-giving (Otake & Hagenimana, 2021). Rituals in gift-giving have been going on for centuries by different religions.…”
Section: The Socio-cultural Side Of Gift-givingmentioning
confidence: 99%
“…In Japanese culture, buying food from seven neighbours for a 7-year-old child is interpreted as sacrificing power from others (Befu, 1968). A tribe in Rwanda sees the gift given to them as a gift from god because of the well-being of gift-giving (Otake & Hagenimana, 2021). Rituals in gift-giving have been going on for centuries by different religions.…”
Section: The Socio-cultural Side Of Gift-givingmentioning
confidence: 99%
“…While collecting data from research participants living in a monetarily poor community, Otake and Hagenimana's ethnographic study conducted in post-genocide Rwanda described a rich "gift economy" whereby community members exchanged goods and services in a form of circular economy [44]. The authors concluded that subjective well-being can be achieved through gifting and sharing, especially when communities have access to resources such as an abundant natural environment, social cohesion, cultural identity, and spirituality.…”
Section: Outliersmentioning
confidence: 99%
“…The authors concluded that subjective well-being can be achieved through gifting and sharing, especially when communities have access to resources such as an abundant natural environment, social cohesion, cultural identity, and spirituality. Otake and Hagenimana claim that the findings of their ethnography contribute to "understanding the detailed process and mechanisms of why and how people can be happy without money" [44] (p. 939), and that subjective well-being can be realised even in communities that are financially impoverished and have experienced disruptive change. Arguably, there is a need for more studies such as Otake and Hagenimana's ethnography, which reveals a positive pathway towards achieving the SDGs while balancing the needs of the environment and economy.…”
Section: Outliersmentioning
confidence: 99%
“…Social DC is adopted to evaluate the social performances of sustainable infrastructure development. From a social benefit aspect, public wellbeing, public participation, and social mobilization have been emphasized in measuring infrastructure sustainability (Otake & Hagenimana, 2021; Schapper et al, 2020). Gansmo (2012) identified that better low‐carbon societies cannot be achieved without community stakeholders' engagement during planning.…”
Section: Theoretical Points Of Departurementioning
confidence: 99%